Ortung – die multimediale Vermessung eines Militärstandortes: Postmoderne Geschichtsschreibung im Dokumentarfilm - Edinger, Kathrina (transcript, 2015)
»Positioning« is a book accompanying the documentary film of the same name, but it is also a profound reflection on postmodern multimedia perception, and on the construction that we call »history«.